The petrological characteristics and significance of organic-rich shale in the Chang 7 member of the Yanchang Formation, south margin of the Ordos basin, central China - Sen Li (KeAi Communications Co., Ltd., 2019)
Abstract The organic-rich shale of the Chang 7 member is the most important source rock in the Ordos basin. The sedimentary environment and the controlling factors of organic matter enrichment, however, are still in contention. In this investigation, the Yishicun outcrop, located on the south margin of the Ordos basin, has been considered for the study. X-ray diffraction, polarizing microscopy, field emission scanning electron microscopy and cathodoluminescence (CL) were used to investigate the petrological features of the organic-rich shale. The content of volcanic ash and the diameter of pyrite framboid pseudocrystals were measured to illustrate the relationship between oxygen level, ash content and the enrichment of organic matter. It has been found that the diameter of pyrite framboid pseudocrystals has a strong correlation with the total organic carbon, demonstrating that the redox status degree of the water column has a positive impact on the enrichment of organic matter. Additionally, with an increase in the ash content, the content of organic matter increased at first and then decreased, and reached a maximum when the ash content was about 6%, illustrating that the ash input has a double effect on the enrichment of organic matter.